Evaluating an Eight-Week Therapeutic Swimming Program in Children with Autism Spectrum Disorder: A Mixed-Methods Study from Romania - Alecu Stefan; Onea Gheorghe Adrian (My University, 2025)
Background/Objectives: In Romania, therapeutic program programs for children with autism spectrum disorder (ASD) focus mainly on behavioral and educational approaches, with limited integration of adapted physical activity (APA). Therapeutic swimming may provide complementary benefits, addressing both physical and psychosocial challenges. This study explored parent-perceived changes across an adapted therapeutic swimming program, following ABA therapy, on the well-being, learning, attention, physical activity, and social functioning of children with ASD. A custom-developed parent-report tool (PPQ-Autism-Swim) was used to measure perceived changes across key developmental domains. Methods: Thirty-nine children with ASD were recruited, of whom 36 completed the full 8-week swimming intervention. Parent-report questionnaires, developed by behavioral therapists under the supervision of a clinical psychologist, were administered at three time points: 8 weeks before swimming (T − 8), immediately before swimming after Applied Behaviour Analysis (ABA) therapy (T0), and 8 weeks after swimming (T + 8). The questionnaire assessed five subscales: general well-being, physical activity and energy, attention and focus, learning and cognitive progress, and self-confidence and social behaviors. Data were analyzed using descriptive statistics, repeated-measures ANOVA, and thematic analysis of qualitative parental feedback. ABA therapy served as a behavioral baseline, allowing comparison with subsequent gains from swimming. Results: Parents reported higher scores across time points, suggesting perceived changes in several domains. From T − 8 to T0, moderate gains followed ABA therapy, while from T0 to T + 8, therapeutic swimming was associated with improvements. At T + 8, 35 of 36 children showed measurable progress, particularly in physical activity regulation and self-confidence. Parental feedback emphasized calmer behavior, improved sleep, increased social interaction, and greater pride in new skills. Reliability testing indicated good to excellent internal consistency (Cronbach’s α = 0.78–0.91). Conclusions: Therapeutic swimming appears to be an effective and motivating form of adapted physical education, complementing behavioral therapies and addressing multiple developmental challenges in children with ASD.
Keywords: autism spectrum disorder; adapted physical activity; therapeutic swimming; aquatic therapy; Romanian; parental perception; child development